Quantitative evaluation of chimerism status following haematopoeitic stem cell transplantation using a microchip electrophoresis system - Daud, S.S.; Ibrahim, K.; Ariffin, Hany (Faculty of Medicine, University of Malaya, 2007)
We aimed to establish a method for quantitative analysis of mixed haematopoietic chimerism based on microchip electrophoresis of selected molecular markers following PCR amplification for accurate monitoring of graft status post-transplantation. A 12-year-old girl with relapsed acute lymphoblastic leukaemia who underwent allogeneic bone marrow transplantation had qualitative chimerism analysis using short tandem repeat markers at three time points following the procedure. Her archived DNA samples were then used to test the ability to correlate her clinical course with changes in the quantity of donor chimerism at the different time points. Quantitative chimerism analysis was performed on the Agilent 2100 bioanalyser and donor-recipient ratios were calculated from generated electropherograms. Complete donor chimerism (98%) was demonstrated three weeks post- transplantation. Decreasing amount of donor chimerism to 24% was shown after three months and this concurred with clinical relapse. Following a second transplant, full donor chimerism was reestablished where donor chimerism rose to 100%. High resolution microchip electrophoresis could be useful in predicting the occurrence of increasing recipient chimerism which may herald impending relapse in patients while the disease burden is still low. This investigational approach may provide useful information for clinicians to select appropriate intervention strategies to ensure successful transplantation.